Everyday cosmopolitanism of refugee entrepreneurs - Ivanova-Gongne, Maria; Lång, Stefan; Muhos, Matti; Saarela, Martti (Emerald, 2026)
Purpose
This study explores how refugee entrepreneurs engage in everyday cosmopolitan practices as they navigate underdog entrepreneurship to shape their business development and interactions with the host society.
Design/methodology/approach
Focusing on six refugees from the Middle East in Finland, narrative analysis with a holistic content approach is used to interpret the data.
Findings
Refugee entrepreneurs consistently engage in everyday cosmopolitanism through diverse interactions, fostering personal and business growth while benefiting the host community. By navigating the challenges of underdog entrepreneurship through strategically engaging in everyday cosmopolitan practices, they challenge elite associations of cosmopolitanism, overcome systemic barriers, exercise agency in constrained contexts and exert voice in an attempt to influence social norms.
Originality/value
This paper advances understanding of everyday cosmopolitanism among refugee entrepreneurs by arguing that everyday cosmopolitan practices function as active, entrepreneurial strategies enabling refugees to overcome systemic barriers and exercise their socioeconomic agency. Furthermore, it looks beyond pragmatic application of cosmopolitanism to stress its moral dimension by highlighting how everyday cosmopolitanism fosters universal values, such as cultural openness and equality. It also extends underdog entrepreneurship literature to include refugee experiences, which have been previously overlooked or grouped with those of migrants, despite their distinct structural challenges. Practical implications highlight the importance of a two-way integration through practices of everyday cosmopolitanism, both from refugees and local society.